Culture in healthcare organisations - Burnett, Keith (Henry Stewart Talks, 2026)
"Strong" culture in healthcare, Harmful bullying environments, why measuring culture falls short, Cultural diversity in healthcare, Professional hierarchy tensions, Psychological safety, Change through collaboration